MURABAHAH AND MUSYARAKAH MUTANAQISAHCONTRACTS WITH PROFIT LOSS SHARING METHODIN ISLAMIC HOME FINANCING - Aulia Kusuma Putri, Shafina
Islamic banking in Indonesia has experienced rapid growth in recent years, offering various financing products in accordance with Sharia principles, one of which is Sharia Home Ownership Financing (KPR Syariah). This final project aims to analyze the Sharia KPR financing model that provides the most optimal rate of return between murabahah and musyarakah mutanaqisah (MMQ) contracts using the profit-loss sharing method, which will be applied to a specific case. The profit-sharing ratio (nisbah) in the MMQ contract can be determined based on the customer’s ownership proportion or set according to the agreement made at the contract’s inception. Simulations are conducted based on assumptions relevant to the example of a Sharia KPR financing product. Using the discussed case, the simulation results show that the highest rate of return is obtained from the musyarakah mutanaqisah model with a floating ratio, followed by musyarakah mutanaqisah with a fixed ratio, and lastly murabahah. The optimal fixed ratio is achieved when the difference between the property price and the customer’s equity at the end of the financing period is less than the specified error margin. An increase in average unexpected costs results in a decrease in the rate of return for all models, while volatility in unexpected costs causes the rate of return to become more fluctuating